Do indesejado ato de lembrar ao desejo de esquecer: uma análise do processual esquecimento de Júlia em Como esquecer - anotações quase inglesas - Freire, Keila de Sousa (2019)
This research presents a reading about the novel How to forget: Almost English notes (2010), by the Brazilian writer Myriam Campello (1948-). The purpose of this study is to analyze the forgetfulness through a slant with a positive value, in opposition to our Western culture that contain in memory and in the act to remember, what should be intended for the beings in their social coexistences. Julia, an English literature university professor, is the protagonist and narrator of this plot who narrates about griefs, sorrows and destroyed affections after the abrupt match of Antonia, her partner. To structure the discussion, we study the memory theories developed by Agostinho (2001), Le Goff (1990), Bergson (1999), Halbwachs (2003), Ricoeur (2007) and Deleuze & Guattari (2004), with the intention to establish the schizoanalysis of memory concept, a term that will perform as our analytical basis. Through this concept, Julia and her loss will be observed as an only and unrepeatable experience. According to her, the act of forget is a desired element and to achieve the forgetfulness is an event that will bring relief to the protagonist. At that, therefore, we elicit the conception about the happy forgetfulness with the objective to understand how Julia trace her progress seeking answers for her procedural forgetfulness. All the journey ends with the development of hypotheses to the question that inspired our research: How to forget (?).